AKHLAK BELAJAR AL-QUR’AN PESERTA DIDIK DAN IMPLEMENTASINYA DI MTS NEGERI 41 AL-AZHAR ASY-SYARIF JAKARTA - Abdul Qohiru (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
The focus of this research is about the morals of learning the Koran students must have which include: Sincere, Clean Mouth, In Holy Conditions, Clean Places, Familiarize Starting Every Surah with Basmalah, Sprinkling Verses, and Respecting the Qur'an. The conclusions of this study are: First: Prioritizing the sanctity of the soul from ignoble morals. Because science is devotion to the heart, prayer heart, and the soul's approach to Allah Ta'ala. The effort to gain knowledge and knowledge is the practice of the heart. The science of cleaning hidden impurities (hearts) and leading to the Creator. Second: A student must not be arrogant with his knowledge and do not oppose his teacher. But surrender entirely to the teacher with confidence in all his advice, like a sick fool who is to his experienced doctor. Third: A student at the beginning level, should guard himself from listening to people's debates about science. The same thing that he learned was worldly science or the science of lateness. Because such doubts his mind, amazes his heart, weakens his opinion and leads him to despair from knowing and deepening it. This study uses a qualitative approach because of the consideration to directly analyze reality in the field so that the data obtained can be scientifically justified. This study also wants to reveal in a descriptive and in-depth manner about the morals of learning the Qur'an of the students and its implementation in state MTs 41 Al Azhar Asy Syarif Jakarta.